Treating low back pain in athletes: a systematic review with meta-analysis. Issue 12 (21st December 2020) - Thornton, Jane S; Caneiro, J P; Hartvigsen, Jan; Ardern, Clare L; Vinther, Anders; Wilkie, Kellie; Trease, Larissa; Ackerman, Kathryn E; Dane, Kathryn; McDonnell, Sarah-Jane; Mockler, David; Gissane, Conor; et al.
Abstract : Objective: To summarise the evidence for non-pharmacological management of low back pain (LBP) in athletes, a common problem in sport that can negatively impact performance and contribute to early retirement. Data sources: Five databases (EMBASE, Medline, CINAHL, Web of Science, Scopus) were searched from inception to September 2020. The main outcomes of interest were pain, disability and return to sport (RTS). Results: Among 1629 references, 14 randomised controlled trials (RCTs) involving 541 athletes were included. The trials had biases across multiple domains including performance, attrition and reporting. Treatments included exercise, biomechanical modifications and manual therapy. There were no trials evaluating the efficacy of surgery or injections. Exercise was the most frequently investigated treatment; no RTS data were reported for any exercise intervention. There was a reduction in pain and disability reported after all treatments. Conclusions: While several treatments for LBP in athletes improved pain and function, it was unclear what the most effective treatments were, and for whom. Exercise approaches generally reduced pain and improved function in athletes with LBP, but the effect on RTS is unknown. No conclusions regarding the value of manual therapy (massage, spinal manipulation) or biomechanical modifications alone could be drawn because of insufficient evidence. High-quality RCTs are urgently needed to determine the effect of commonly used interventions in treating LBP in athletes.